Notes on the uniqueness of meromorphic functions concerning differential polynomials - Fengrong Zhang; Linlin Wu (Journal of Inequalities and Applications, 2019)
Abstract This paper is devoted to the uniqueness problem on meromorphic functions whose differential polynomials share one nonzero finite constant. We improve some previous results and answer two open problems posed by Dyavanal.